Dimensi Ekologis dalam Leksikon Ritual Lewak Tapo: Representasi Kearifan Lokal Masyarakat Witihama - Fransiska Jone Mare (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to identify the forms and classifications of ecolexicons, analyze the ecological dimensions embedded within them, and reveal the local wisdom values represented in the Lewak Tapo ritual. This research employs a descriptive qualitative method with the ecolinguistic model of Bang and Door as the analytical framework. The data consist of ritual utterances obtained through observation, in-depth interviews, and note-taking techniques involving molan (traditional ritual leaders) and customary elders in Witihama Village. Data analysis was conducted through several stages, namely data reduction, ecolexicon classification, descriptive-interpretative data presentation, and conclusion drawing based on the ecological dimensions found in the ritual utterances. The findings show that the ecolexicons in the Lewak Tapo ritual reflect three ecological dimensions: ideological, sociological, and biological dimensions. These dimensions are interconnected in constructing a system of meaning that represents local wisdom values, such as respect for life, mutual cooperation, religiosity, and obedience to customary norms. This study confirms that language in traditional rituals functions not only as a means of communication but also as a medium for preserving ecological knowledge and the cultural identity of the community. This study is limited by the small number of informants and the focus on only one customary area, which may not fully represent the diversity of ritual practices within the Lamaholot community. Therefore, future studies are recommended to investigate similar traditional rituals in other cultural regions using interdisciplinary approaches in order to gain a more comprehensive understanding of the relationship between language, ecology, and local culture.